Month of birth and the risk of developing type 1 diabetes among children in the Swedish national Better Diabetes Diagnosis Study - Hedlund, Emma; Ludvigsson, Johnny; Elding Larsson, Helena; Forsander, Gun; Ivarsson, Sten; Marcus, Claude; Samuelsson, Ulf; Persson, Martina; Carlsson, Annelie (Acta Paediatrica, 2022)
Aim Previous studies have reported an association between month of birth and incidence of type 1 diabetes. Using population‐based data, including almost all newly diagnosed children with type 1 diabetes in Sweden, we tested whether month of birth influences the risk of type 1 diabetes. Methods For 8761 children diagnosed with type 1 diabetes between May 2005 and December 2016 in the Better Diabetes Diagnosis study, month of birth, sex and age were compared. Human leucocyte antigen (HLA) genotype and autoantibodies at diagnosis were analysed for a subset of the cohort (n = 3647). Comparisons with the general population used data from Statistics Sweden. Results We found no association between month of birth or season and the incidence of type 1 diabetes in the cohort as a whole. However, boys diagnosed before 5 years were more often born in May (p = 0.004). We found no correlation between month of birth and HLA or antibodies. Conclusion In this large nationwide study, the impact of month of birth on type 1 diabetes diagnosis was weak, except for boys diagnosed before 5 years of age, who were more likely born in May. This may suggest different triggers for different subgroups of patients with type 1 diabetes.